(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This academic article explores the significant clinical importance of thromboembolism, specifically venous thromboembolism (VTE), deep vein thrombosis (DVT), and pulmonary embolism (PE). It thoroughly analyzes the pathophysiological mechanisms, etiological factors, and the role of Virchow’s triad. The article details diagnostic algorithms, including D-dimer testing and imaging methods, alongside therapeutic approaches, acute and long-term anticoagulant management, and prevention strategies. Finally, it discusses complications, prognosis, chronic sequelae management, and future research directions in the field.